Contamination of multidose butorphanol vials in small animal general practices. (November 2015) - Bell, A.; Yamaoka, T. T.; Akil, L.; Watson, D.; Devine, C.
Abstract : OBJECTIVES: To assess and quantify medetomidine contamination of butorphanol multidose vials in small animal general practices and determine if practice policies and procedures regarding drug handling, as determined by questionnaire, impact upon contamination level. METHODS: Samples of butorphanol were withdrawn from in‐use vials in participating practices in June and July 2013. Samples were analysed using high‐performance liquid chromatography and mass spectrometry. RESULTS: Forty‐one samples were obtained from 31 practices. Contamination was detected in 29 samples from 10 mL vials. The mean (αsd) contamination was 0 · 275 (α0 · 393) µg/mL; maximum contamination in any vial was 2 · 034 µg/mL. There was no correlation between volume of the vial used and the level of contamination. None of the survey factors predicted contamination levels of the vials. CLINICAL SIGNIFICANCE: Contamination of butorphanol multidose vials with medetomidine was common but the level of contamination was insufficient to cause detrimental effects in dogs if butorphanol were to be administered alone. The potential for sporadic higher levels of contamination must be taken into account, especially when using 50 mL vials when sedating critically ill cases, because there is a risk of clinical side effects.